2021
DOI: 10.4314/as.v20i1.5
|View full text |Cite
|
Sign up to set email alerts
|

Carcass and organ characteristics of finishing broilers fed diets containing probiotics (Saccharomyces cerevisiae)

Abstract: A five-week study was conducted to determine the effect of feeding varying levels of S. cerevisiae on carcass and organ characteristics of finishing broilers. One hundred and twenty 4-weeks old broilers of cobb strain were randomly assigned to four treatments (T1 = 0.6 g Saccharomyces cerevisiae (SC) kg–1 diet; T2 = 0.8 g SC kg–1 diet; T3 = 1.0 g SC kg–1 diet and T4 = 0.0 g SC kg–1 diet) with 30 birds per treatment and replicated twice with 15 birds per replicate in a completely randomized design. Feed and wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Moreover, yeast-included group significantly increased BWG and FCR while FI remained unchanged (Eltazi et al 2014). Nevertheless, inclusion of S. cerevisiae (Ugwuoke et al 2021) and GEO (Kırkpınar et al 2011) in broiler diets showed no significant difference among BWG, FI, and FCR. In agreement with the current study, Ahmed et al (2015) noted that the growth response (BWG, FI) significantly increased in broilers fed with different levels of S. cerevisiae.…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, yeast-included group significantly increased BWG and FCR while FI remained unchanged (Eltazi et al 2014). Nevertheless, inclusion of S. cerevisiae (Ugwuoke et al 2021) and GEO (Kırkpınar et al 2011) in broiler diets showed no significant difference among BWG, FI, and FCR. In agreement with the current study, Ahmed et al (2015) noted that the growth response (BWG, FI) significantly increased in broilers fed with different levels of S. cerevisiae.…”
Section: Discussionmentioning
confidence: 89%
“…These probiotics produce enzymes and vitamins and have antioxidant and microbial properties [21]. Live yeasts of the genus Saccharomyces have also shown probiotic activity in farm animals, modifying the intestinal microbiota, reducing the risk of dysbiosis and producing vitamins and enzymes [22,23]. Those most often used are Saccharomyces boulardii and Saccharomyces cerevisiae [24].…”
Section: Introductionmentioning
confidence: 99%